Synthesis and Characterization of Composites-Based Bacterial Cellulose by Ex-Situ Method as Separator Battery - Sarkono; Maria Ulfa; Inda Noviani; Emmy Yuanita; Ni Komang Tri Dharmayani; Sudirman (Jurnal Penelitian Pendidikan IPA, 2023)
Many studies have been conducted and developed on cellulose-based battery separator materials, including bacterial cellulose, which has characteristics like plant cellulose. This research aims to synthesize BC/Al2O3 composite and analyze its potential as a battery separator. The synthesis of the composite with the ex-situ method is to immerse BC from tofu liquid waste (fermentation time variation of 6, 7, and 8 days) into Al2O3 suspension. The characterization results showed that the immersion of Al2O3 in BC can increase porosity, electrolyte absorption, and conductivity, indicating that the composite has the potential to be used as a battery separator.